(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
Orchid is an ornamental plant commodity with a high contribution to horticultural production in Indonesia. Efforts to fulfill market demand have caused the hybridization of many orchids to improve quality and create uniqueness in orchid horticulture. Hybridization is influenced by the genetic distance between orchid species to be crossing over. This study aimed to analyze the genetic relationship of the Indonesian endemic Orchidaceae family using sequence alignment and genetic distance. This descriptive exploratory research uses the bioinformatics method with the genetic distance as a variable. The procedure in this study begins with collecting sequence data in FASTA format, aligning sample sequence data, constructing phylogenetic trees, computing amino acid composition, computing Pairwise Distance, and ends with data analysis. The sample was 16 species of orchids that were selected using a purposive sampling technique with complete sequence data in GenBank. The genetic relationships of the 16 species consist of two major clades. Each clade has a pair of species connected by a straight vertical line indicating genetic distance <0.003 or close category. In the first clade, there are three pairs of closely related species (Vanda pumila – Dendrobium trilamellatum, Cymbidium dayanum – Aerides odorata, and Coelogyne pandurata – Coleogyne asperata). While in the second clade, only one pair of species is closely related, namely Phalaenopsis corningiana – Phalaenopsis tetrapis. This research information confirms the DNA-based identification of endemic Indonesian orchids, which has a positive impact on the accuracy of biodiversity inventory and monitoring. This research supports SDG 5. The data provides a scientific basis for terrestrial ecosystem conservation and prevents biodiversity loss through more accurate species identification.